Population Genetic Analysis of Modern and Ancient DNA Variations Yields New Insights Into the Formation, Genetic Structure, and Phylogenetic Relationship of Northern Han Chinese - Chen, Pengyu; Wu, Jian; Luo, Li; Gao, Hongyan; Wang, Mengge; Zou, Xing; Li, Yingxiang; Chen, Gang; Luo, Haibo; Yu, Limei; Han, Yanyan; Jia, Fuquan; et al. (Frontiers in Genetics, 2019)
Modern East Asians derived from the admixture of aborigines and incoming farmers expanding from Yellow and Yangtze River Basins. Distinct genetic differentiation and subsequent admixture between North East Asians and South East Asians subsequently evidenced by the mitochondrial DNA, Y-chromosomal variations and autosomal SNPs. Recently, population geneticists have paid more attention to the genetic polymorphisms and background of southern-Han Chinese and southern native populations. The genetic legacy of northern-Han remains uncharacterized. Thus, we performed this comprehensive population genetic analysis of modern and ancient genetic variations aiming to yield new insight into the formation of modern Han, and the genetic ancestry and phylogenetic relationship of the northern-Han Chinese population. We first genotyped 25 forensic associated markers in 3,089 northern-Han Chinese individuals using the new-generation of the Huaxia Platinum System. And then we performed the first meta-analysis focused on the genetic affinity between Asian Neolithic ancients and modern northern-Han Chinese by combining mitochondrial variations in 417 ancient individuals from 13 different archeological sites and 812 modern individuals, as well as Y-chromosomal variations in 114 ancient individuals from 12 Neolithic sites and 2,810 modern subjects. We finally genotyped 643,897 genome-wide nucleotide polymorphisms (SNPs) in 20 Shanxi Han individuals and combined with 1927 modern humans and 40 Eurasian ancient genomes to explore the genetic structure and admixture of northern-Han Chinese. We addressed genetic legacy, population structure and phylogenetic relationship of northern-Han Chinese via various analyses. Our population genetic results from five different reference datasets indicated that Shanxi Han shares a closer phylogenetic relationship with northern-neighbors and southern ethnically close groups than with Uyghur and Tibetan. Genome-wide variations revealed that modern northern-Han derived their ancestry from Yakut-related population (25.2%) and She-related population (74.8%). Summarily, the genetic mixing that led to the emergence of a Han Chinese ethnicity occurred at a very early period, probably in Neolithic times, and this mixing involved an ancient Tibeto-Burman population and a local pre-Sinitic population, which may have been linguistically Altaic.